Putative morphology of Neoehrlichia mikurensis in salivary glands of Ixodes ricinus - Ondruš, Jaroslav; Kulich, Pavel; Sychra, Oldřich; Široký, Pavel (Scientific reports, 2020)
Neoehrlichia mikurensis is an emerging tick-borne intracellular pathogen causing neoehrlichiosis. Its putative morphology was described in mammalian, but not in tick cells. In this study, we aim to show the presumptive morphology of N. mikurensis in salivary glands of engorged females of Ixodes ricinus. To accomplish this, we collected I. ricinus ticks in a locality with a high N. mikurensis prevalence, allowed them to feed in the artificial in vitro feeding system, dissected salivary glands and screened them by PCR for N. mikurensis and related bacteria. Ultrathin sections of salivary glands positive for N. mikurensis but negative for other pathogens were prepared and examined by transmission electron microscopy. We observed two individual organisms strongly resembling N. mikurensis in mammalian cells as described previously. Both bacteria were of ovoid shape between 0.5-0.8 μm surrounded by the inner cytoplasmic and the rippled outer membrane separated by an irregular electron-lucent periplasmic space. Detection of N. mikurensis in salivary glands of I. ricinus suggests that this bacterium uses the "salivary pathway of transmission" to infect mammals.
Keywords: transmisní elektronová mikroskopie; Ixodes; Anaplasmataceae; DNA, Bacterial; DNA bakterií; krmivo pro zvířata; klíště; Animals; Female; ženské pohlaví; Microscopy, Electron, Transmission; Salivary Glands; zvířata; Animal Feed; slinné žlázy